Correlation Between Hallux Valgus Severity, Abductor Hallucis Muscle Properties, and Plantar Pressure Distribution - Kyeong-Ah Moon; Ye Jin Kim; Hye-Seon Jeon (Physical Therapy Korea)
Background: Hallux valgus (HV) is a common foot deformity in which the great toe deviates laterally and the first metatarsal deviates medially, leading to pain, discomfort, and reduced mobility. HV severity is typically assessed using the hallux valgus angle (HVA) and intermetatarsal angle (IMA). Objects: This study aimed to explore how changes in skeletal, muscular, and functional variables correlate with HV severity and to provide evidence for more integrated treatment approaches. Methods: Sixty volunteers with mild to moderate bilateral HV (HVA 15–40 degrees) participated. The measurements included HVA and IMA via radiography, abductor hallucis muscle (AbdH) cross-sectional area (CSA) and tone using ultrasound and Myoton PRO, range of motion (ROM) of the ankle and great toe metatarsophalangeal (MTP) joint with a goniometer, and plantar pressure during gait with a Zebris FDM system. Pearson’s correlation coefficient was used for the statistical analysis. Results: An Increased HVA was associated with a higher IMA (r = 0.858, p < 0.05). The HVA was inversely related to the AbdH CSA (r = –0.337, p < 0.05) and muscle tone (r = –0.889, p < 0.01). With increasing HVA, dorsiflexion ROM of the ankle (r = –0.307, p < 0.01) and both flexion (r = –0.197, p < 0.05) and extension (r=-0.182, p<0.05) ROM of the great toe MTP joint decreased. Conversely, ankle plantar flexion ROM increased with the HVA (r = 0.312, p < 0.01). Additionally, plantar pressure increased in the second metatarsal areas (r = 0.457, p < 0.05) a with higher HVA. Conclusion: This study demonstrates significant correlations between HV severity and various biomechanical factors, highlighting the need for comprehensive treatment strategies. While stretching the adductor hallucis muscle and strengthening the AbdH have been widely recognized interventions for HV, our findings provide evidence that ROM exercises for the ankle and the MTP joint of the great toe are also critical components of a physical therapy program for managing HV. Longitudinal studies are required to assess the effectiveness of these approaches.